New and poorly known species of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from Nepal - Shavrin, Alexey V. (Zootaxa, 2012)
Lesteva (s.str.) jaegeri sp. n. from Nepal (Annapūrna Himal, Manaslu Himal) is described. L. (s.str.) fluviata Champion, 1920 is redescribed. Lesteva (s.str.) championi Lohse, 1982 is recorded from Pakistan for the first time. Aedeagi of all species are illustrated. An identification key to the Lesteva Latreille, 1797 of Nepal is provided.